2020
DOI: 10.1177/1369148120947956
|View full text |Cite
|
Sign up to set email alerts
|

Theorising backlash politics: Conclusion to a special issue on backlash politics in comparison

Abstract: This conclusion to a special issue on backlash politics develops a proto-theory of backlash politics. The special issue’s introduction defined backlash politics as a particular form of political contestation with a retrograde objective as well as extraordinary goals or tactics that has reached the threshold level of entering mainstream public discourse. While a sub-category of contentious politics, we argue that backlash politics is distinct and should not be understood as ‘regressive contentious politics’. Dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Britain has left the EU, but we should be sceptical of Boris Johnson’s (2020) claim, on the eve of this exit, that Britain is ushering in a new era for itself in which it is both ‘a great European power’, and one ‘truly global in our range and ambitions’. ‘Backlash politics may succeed in their extraordinary objectives’, Alter and Zürn (2020b, this issue) explain, when they ‘[reconstitute] the polity to fit the vision of the movement’. Where does Brexit leave us then?…”
Section: Resultsmentioning
confidence: 99%
“…Britain has left the EU, but we should be sceptical of Boris Johnson’s (2020) claim, on the eve of this exit, that Britain is ushering in a new era for itself in which it is both ‘a great European power’, and one ‘truly global in our range and ambitions’. ‘Backlash politics may succeed in their extraordinary objectives’, Alter and Zürn (2020b, this issue) explain, when they ‘[reconstitute] the polity to fit the vision of the movement’. Where does Brexit leave us then?…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that dominant group members can resist equity‐oriented change depending on how the inequality and their own advantage is framed (Lowery et al., 2012; Rosette & Koval, 2018), and can also have social change motives that are regressive, meaning motives that seek to maintain or increase inequality (Sweetman et al., 2013). Regressive change motives are usually framed under backlash politics (Alter & Zürn, 2020), referring to the aim of powerful groups to regain power that has been lost or is threatened (Mansbridge & Shames, 2008). Taking this argument a step further, we propose that regressive social change can also occur when the dominant group is purposefully inactive for the sake of preserving the status quo.…”
Section: A Normative Framework Of System‐supporting Inactionmentioning
confidence: 99%
“…Researchers have suggested that when the disadvantaged openly share their discontent and grievances, the powerful have no other choice than to engage in (violent) backlash. Such backlash is considered a special form of contentious politics with separate causes, mediators and outcomes (Alter & Zürn, 2020; Shepherd et al., 2018). It is evident, for example, in the rise of populist sentiments, such as anti‐feminism, and pushback against reproductive rights and immigrant groups, which have received ample media and research attention (e.g., Clarke, 2021).…”
Section: A Conceptual Model Of Privilege Maintenancementioning
confidence: 99%
“…Stie (2021) argues that a growing range of crises show that the 'input' legitimacy of the EU cannot be divorced from 'output' legitimacy -just because IRAs are effective in regulating the quality of goods in the Single Market does not make the EU immune from allegations of a 'democratic deficit'. Alter and Zürn (2020) and Zürn (2021) have even theorised that the growth of IRAs can be linked to the growth in electoral politics of authoritarian populism, via a 'backlash' against so-called 'liberal elite' unelected bodies. Key questions have hence been raised about the practices of IRAs to promote democratic values of inclusion, diversity and engagement (Schmidt and Wood, 2019).…”
Section: Iras and The Eu's 'Democratic Deficit'mentioning
confidence: 99%